DEDAYA (Desa Berdaya): Independent Economic Development of Poncokusumo Village Community Through Orange Peel Waste Processing to Create Village Independent Income - Latifa Al Muta Ali; Amanda Rahadatul Aisy; Adhiwa Restuanggara Saeputra; Nora Silvia Siahaan; Yogi Riyandika; Endang Sri Redjeki (Journal of Law, Politic and Humanities, 2024)
Poncokusumo Village, located in Poncokusumo Subdistrict, Malang Regency, has significant potential in orange and apple cultivation. The 484-hectare area is estimated to produce 1.8 tons of commodities per 1000 square meters. The DEDAYA program aims to develop a self-sustaining economy in Poncokusumo Village, thereby achieving village independent income and enhancing the village’s strengths through the utilization of orange peel waste into products such as tekaje flour, o-jie-tea, orange chili sauce, and eco-enzyme. This solution involves a holistic approach through (1) socialization and business assistance in developing and managing orange peel waste, and (2) the establishment of the DEDAYA (Desa Berdaya) institution responsible for the structured management of the program. The outcomes include processed orange peel products and scientific publications in Sinta 3 journals. The program’s success is measured by training existing entrepreneurs and enhancing the role of local institutions in supporting village independent income through the DEDAYA program